2012
DOI: 10.1002/pro.2069
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial outer membrane β‐barrel assembly machinery

Abstract: b-Barrel proteins found in the outer membrane of Gram-negative bacteria serve a variety of cellular functions. Proper folding and assembly of these proteins are essential for the viability of bacteria and can also play an important role in virulence. The b-barrel assembly machinery (BAM) complex, which is responsible for the proper assembly of b-barrels into the outer membrane of Gram-negative bacteria, has been the focus of many recent studies. This review summarizes the significant progress that has been mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
116
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 107 publications
3
116
0
Order By: Relevance
“…Furthermore, in the outer membrane of mitochondria, a similar integrated supercomplex, containing the translocase of the outer membrane (TOM) and the sorting and assembly machinery (SAM, a homolog of the BAM complex), was reported to function in mitochondrial ␤-barrel OMP biogenesis (31). In chloroplasts, ␤-barrel OMP biogenesis involves the outer membrane translocon TOC, the inner membrane translocon TIC, and the assembly protein Toc-75V, a homolog of bacterial BamA (11). The question of whether a similar integrated supercomplex is also formed in chloroplasts certainly merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the outer membrane of mitochondria, a similar integrated supercomplex, containing the translocase of the outer membrane (TOM) and the sorting and assembly machinery (SAM, a homolog of the BAM complex), was reported to function in mitochondrial ␤-barrel OMP biogenesis (31). In chloroplasts, ␤-barrel OMP biogenesis involves the outer membrane translocon TOC, the inner membrane translocon TIC, and the assembly protein Toc-75V, a homolog of bacterial BamA (11). The question of whether a similar integrated supercomplex is also formed in chloroplasts certainly merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The ␤-barrel OMP assembly machine (i.e. the BAM complex) protein BamA, which has homologues in mitochondria (designated as Sam50) and chloroplasts (designated as Toc75), consists of a ␤-barrel domain that is integrated in the outer membrane and a POTRA (polypeptide translocation-associated) domain that extends into the periplasmic space (11). Genetic and biochemical observations showed that BamA is essential for the folding and membrane insertion of ␤-barrel OMPs (5,9,12,13).…”
mentioning
confidence: 99%
“…One of the unique features of the outer membrane of Gramnegative bacteria-as well as those of mitochondria and chloroplasts-is its high content of b-barrel outer membrane proteins (OMPs) [10][11][12][13][14][15] . In bacteria, the biogenesis of b-barrel OMPs depends on the b-barrel assembly machinery (BAM), which in g-proteobacteria is composed of five components, named BamA-E.…”
mentioning
confidence: 99%
“…In bacteria, the biogenesis of b-barrel OMPs depends on the b-barrel assembly machinery (BAM), which in g-proteobacteria is composed of five components, named BamA-E. The central BAM component, BamA, itself is a b-barrel protein that belongs to the Omp85 family [10][11][12][13][14][15] . Omp85 family members function in the intramembrane formation of bbarrels, while another group, represented by the above-mentioned TpsB proteins, facilitates translocation of the TpsA passenger proteins across the outer membrane.…”
mentioning
confidence: 99%
“…This asymmetric phospholipid and lipopolysaccharide (LPS) bilayer also acts as a scaffold for two major classes of membrane proteins: the integral outer membrane proteins (OMPs) and the lipoproteins (3). Integral OMPs are often referred to as ␤-barrel proteins and are assembled into the OM by the ␤-barrel assembly machinery (BAM) (4,5,6,7,8,9). The BAM complex is composed of five proteins: BamA, which is itself an integral OMP, and the four lipoproteins BamB, BamC, BamD, and BamE, which localize to the inner leaflet of the OM (5,6).…”
mentioning
confidence: 99%